The Dark Side: The Poetics of Toxic Leadership. (August 2015) - Armitage, Andrew
The Problem: Morgan explored in her book What Poetry Brings to Business the deep but unexpected connections between business and poetry. She demonstrated how the creative energy, emotional power, and communicative complexity of poetry relate directly to the practical needs for innovation and problem solving that face business managers, and how poetry can unpack complexity, together with the ability to empathize with, and better understand the thoughts and feelings of others. This, it can be argued, not only aids the creative process of individuals, but it can also help facilitate the entrepreneurial culture of an organization, develop imaginative solutions, and help better understand chaotic environments. However, despite Morgan's welcomed addition, it still remains that there is still a dearth of literature of the use of poetry concerning toxic leadership practices. The Solution: According to Roebuck, reflexive practice can be described as a process of inquiry that facilities appreciation and understanding of contextualized views, deeper learning experiences, the development of ideas, and the conditions for actual change. Therefore, if organizations are not to objectify the creativity of those who aspire to be organizational leaders, then leadership development programs have to give voice to those who own organizational problems and their solution. Examples of organizational poetry will be presented to show how it can be used to unlock personal experiences and relationships within the context of working life. It will be argued that if stories are to represent reality as lived by those who report them, then poetry provides an alternative method of enquiry to inform contemporary leadership practices. The Stakeholders: Poetry empowers individuals to internalize stories that carefully attend to context and settings to offer fresh perspectives on established truths, thus providing a way to explore hidden worlds that might often go unsaid in the milieu of normal conversation. As such, this article is aimed at those who need to develop an alternative paradigm for leadership and Human Resource Development (HRD) educational programs and want to adopt a more open dialogical approach to human relations within classroom settings and practice.